Cost-effectiveness of direct metal laser sintered maraging steel inserts for plastic injection moulding process - Combrinck, J.; Van As, B.; Booysen, G.J.; De Beer, D.J. (South African Journal of Industrial Engineering, 2019)
This paper describes an investigation into the possible heat transfer benefits of conformal cooling channels using maraging steel MS1 inserts, which could result in a reduction of cycle times and cost per product, and improve part quality by eliminating defects such as warpage and heat sinks. A manufacturing cost and lead-time comparison showed that a conventionally manufactured insert reached its break-even point after fewer injection moulding cycles than an additive manufactured insert, due to its lower manufacturing costs. During high-volume production, the additive manufactured insert becomes more profitable to use, due to its shorter cycle times. Hierdie artikel beskryf 'n ondersoek na die moontlike hitteoordrag voordele van vormgetroue verkoelingskanale in martensities-verouderde MS1 insetsels. Dit kan lei tot 'n vermindering in die siklusstye en koste per produk, asook 'n verbetering in die kwaliteit van die vervaardigde komponente deur defekte soos kromtrekking en hitteputte te voorkom. 'n Vergelyking tussen die vervaardigings-koste en -tyd het getoon dat 'n konvensionele vervaardigde insetsel die gelykbreekpunt bereik het na minder spuitgietsiklusse in vergelyking met 'n laag vervaardigde invoegsel vanweë die laer vervaardigingskoste. Tydens hoë volume produksie word die laag-vervaardigde insetsel egter meer winsgewend om te gebruik as gevolg van ŉ korter spuitgietsiklus.